1997
DOI: 10.1891/0886-6708.12.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Keane MMPI-PTSD Scale Against DSM-III-R Criteria in a Sample of Battered Women

Abstract: The Keane, Malloy, & Fairbank (1984) MMPI-PTSD Scale has proven to be a reliable and valid measure of posttraumatic stress disorder (PTSD) in combat veterans. However, few studies have examined the MMPI-PTSD Scale’s validity in civilian trauma victims, including battered women. In the present study, 46 battered women who completed the MMPI-PTSD Scale were assigned to PTSD-Positive and PTSD-Negative groups based on a structured diagnostic interview and then contrasted on the MMPI-PTSD Scale. Significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(26 reference statements)
1
2
0
1
Order By: Relevance
“…In line with previous studies using veteran and civilian trauma samples (Baldrachi et al, 1999; McCaffrey et al, 1989; Perrin et al, 1997), results from this study showed a significant elevation on the PK scale in individuals who developed PTSD after traumatic workplace accidents compared with those who did not develop PTSD after exposure to trauma. A significant proportion of the elevation on the PK scale in this and previous studies, however, appears to be attributable to a higher level of impairment in individuals with PTSD compared with individuals without PTSD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous studies using veteran and civilian trauma samples (Baldrachi et al, 1999; McCaffrey et al, 1989; Perrin et al, 1997), results from this study showed a significant elevation on the PK scale in individuals who developed PTSD after traumatic workplace accidents compared with those who did not develop PTSD after exposure to trauma. A significant proportion of the elevation on the PK scale in this and previous studies, however, appears to be attributable to a higher level of impairment in individuals with PTSD compared with individuals without PTSD.…”
Section: Discussionsupporting
confidence: 92%
“…For example, the PK scale was found to be the most robust scale in distinguishing between veterans with PTSD and those with posttraumatic stress symptomatology who did not meet full criteria for PTSD (Baldrachi, Hilsenroth, Arsenault, Sloan, & Walter, 1999). Other research has examined the predictive capabilities of the PK scale in assessing PTSD in civilian trauma victims (Gaston, Brunei, Koszycki, & Bradwejn, 1996, 1998Koretzky & Peck, 1990;McCaffrey, Hickling, & Marrazo, 1989;Noblitt, 1995;Perrin, Van Hasselt, & Hersen, 1997). With the exception of Gaston et al's, results from these studies with civilian PTSD samples have led many investigators to believe that the MMPI-2 PK scale is able to distinguish civilian patients with PTSD from patients without PTSD across a wide range of samples, including motor vehicle accident victims, physically abused women, and crime victims.…”
mentioning
confidence: 99%
“…A number of mental disturbances have been described in physically abused women: posttraumatic stress disorder (PTSD) [1,2,8,[14][15][16][17][18][19][20][21], depression [1,4,8,[22][23][24][25][26][27][28][29][30], anxiety [25,27,31], sleeping disturbances [32,33], eating disorders [34], social dysfunction, suicide ideation and attempts [7,35,36], and increased likelihood to develop substance abuse behavior [1,13,24,27,28,[37][38][39][40].…”
Section: Consequences Of Intimate Partner Violence On Women Mental Hementioning
confidence: 99%
“…Por ejemplo, Golding (1999) -a partir de un meta-análisis basado en 11 investigaciones-encontró una prevalencia media de este cuadro clínico del 63,8% (con un rango que osciló entre el 31% y el 84,4%). Otras investigaciones -no incluidas en este meta-análisis-ofrecieron tasas de prevalencia similarmente elevadas (Herman, 1992;Vitanza, Vogel y Marshall, 1995;Perrin, Van Hasselt y Hersen, 1997;Echeburúa et al, 1997;Amor et al, 2002). Esta prevalencia media es muy parecida a la que sufren las víctimas de agresiones sexuales (70%) (Amor, Echeburúa, Corral, Zubizarreta y Sarasua, 2001a) y significativamente superior a la existente en la población general de mujeres (entre el 1,3% y el 12,3%) (cfr.…”
Section: Trastorno De Estrés Postraumáticounclassified